Water mass transformation in the Iceland Sea - Kjetil Våge; G.W.K. Moore; Steingrímur Jónsson; Héðinn Valdimarsson (Deep Sea Research Part I: Oceanographic Research Papers, 2015)
The water mass transformation that takes place in the Iceland Sea during winter is investigated using historical hydrographic data and atmospheric reanalysis fields. Surface densities exceeding σθ=27.8kg/m3, and hence of sufficient density to contribute to the lower limb of the Atlantic Meridional Overturning Circulation via the overflows across the Greenland-Scotland Ridge, exist throughout the interior Iceland Sea east of the Kolbeinsey Ridge at the end of winter. The deepest and densest mixed layers are found in the northwest Iceland Sea on the outskirts of the basin׳s cyclonic gyre, largely determined by stronger atmospheric forcing near the ice edge. Much of the accumulated wintertime heat loss in that region takes place during a few extreme cold air outbreak events. Only a small number of hydrographic profiles (2%) recorded mixed layers sufficiently dense to supply the deepest part of the North Icelandic Jet, a current along the slope off northern Iceland that advects overflow water into the Denmark Strait. However, low values of potential vorticity at depth indicate that waters of this density class may be ventilated more regularly than the direct observations of dense mixed layers in the sparse data set indicate. A sudden increase in the depth of this deep isopycnal around 1995 suggests that the supply of dense water to the North Icelandic Jet, and hence to the densest component of the Atlantic Meridional Overturning Circulation, may have diminished over the past 20 years. Concurrent reductions in the turbulent heat fluxes and wind stress curl over the Iceland Sea are consistent with a decrease in convective activity and a weakening of the cyclonic gyre, both of which could have caused the increase in depth of these dense waters. Access to Deep Sea Research - ocean: http://www.sciencedirect.com/science/article/pii/S0967063715000680 Postprint available at www.NACLIM.eu